From Spontaneous Experience to the Cosmos: Arne Næss’ Phenomenology - Valera, Luca (Problemos, 2018)
[full article, abstract in English; only abstract in Lithuanian] The aim of this paper is to focus on Arne Nass’s phenomenological method and some of its anthropological and cosmological implications. Nass’s Ecology, Community and Lifestyle, in fact, can be fruitfully read as an example of phenomenological inquiry, in which the notion of “spontaneous experience” plays a fundamental role. This method leads Nass to develop a “relational ontology,” in which the “ecological self” is seen as a “relational junction within the total field.” In addition, I show how Tymieniecka’s philosophical thought can offer us the proper eco-phenomenological perspective to better understand Nass’s Ecosophy T.